Psychopathology and Occasional Victimization in a Sample of Chilean Students - Rojas Andrade, Rodrigo; Universidad de Chile (Pontificia Universidad Javeriana, 2014)
The objective of this research was to establish the incidence of casual victimization and compare the psychopathological symptoms present in occasional victims and non-victims. A descriptive correlational cross-sectional study was conducted on a sample of 773 from a private school subsidized primary and secondary education in the city of Calama, of both sexes, between 11 and 18 years. Chi-square analysis and t tests for independent samples were performed. The results showed that occasional peer victimization affects 30% of young people and is stable across different ages evaluated. It was found that occasional victims exhibit more depressive, anxious and behavioral symptoms, and also have a lower prosocial behavior compared to the group not victimized. The association between victimization and casual psychopathological problems are discussed.